2000
DOI: 10.3171/spi.2000.93.1.0126
|View full text |Cite
|
Sign up to set email alerts
|

Microendoscopic posterior cervical foraminotomy: a cadaveric model and clinical application for cervical radiculopathy

Abstract: Object. Cervical radiculopathy caused by either soft herniated disc material or foraminal stenosis is a common problem. Anterior and posterior surgical approaches are commonly used to decompress the nerve root. The authors undertook a study to establish the feasibility of performing a microendoscopic posterior approach for cervical foraminotomy in the clinical setting. Methods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…There is a renewed interest by many surgeons with regard to the posterior approach to treat the paracentral and foraminal cervical disc due to the advancements of minimally invasive surgery and endoscopy with a series of reports detailing excellent treatment outcomes as the anterior approach need a more depth in dissection of structures to reach the cervical disc [2,4,12,14,15,22]. Tumialan et al [24] reported that posterior cervical foraminotomy offers a benefit relative to anterior cervical foraminotomy in immediate short-term direct costs and long-term indirect costs, early mobilization and outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a renewed interest by many surgeons with regard to the posterior approach to treat the paracentral and foraminal cervical disc due to the advancements of minimally invasive surgery and endoscopy with a series of reports detailing excellent treatment outcomes as the anterior approach need a more depth in dissection of structures to reach the cervical disc [2,4,12,14,15,22]. Tumialan et al [24] reported that posterior cervical foraminotomy offers a benefit relative to anterior cervical foraminotomy in immediate short-term direct costs and long-term indirect costs, early mobilization and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of the posterior approach include, (1) avoid damage to vital structures located in the anterior area of the cervical spine, (2) avoid the structural and biomechanical damage to the remaining vertebral disc (joint morbidity, bone graft complication, as well as the adjacent joint syndrome) [4,12,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Great advances have been made with the posterior approach with the development of equipment such as the microscope and the endoscope. Advantages of the posterior approach include an ability to avoid damage to vital structures located in the anterior area of the cervical spine (i.e., the trachea, esophagus, internal carotid artery, vertebral artery, thoracic duct, and recurrent laryngeal nerve), an ability to prevent structural and biomechanical damage to the remaining vertebral disc by preserving it, an ability to lower the morbidity associated with the joint, and an ability to reduce the occurrence of complications associated with the bone graft, as well as degenerative changes at the adjacent joint 2,[9][10][11]16,18) . In cases where only dorsal decompression of the nerve root is performed and only fragments of the intervertebral disc are removed, excellent treatment outcomes have also been reported 7,8,12,20) .…”
Section: Introductionmentioning
confidence: 99%
“…and 246g, respectively. On the other hand, the mean surgical time of endoscopic foraminotomy was reported 28-184 minutes and the mean blood loss volume of that was reported no measurable blood loss to 138 ml [14,17,18]. I think that the surgical invasion of MOF is almost equal compare to endoscopic foraminotomy.…”
Section: Discussionmentioning
confidence: 98%